Prospects for the study of the strangeness production within the PHQMD model. (December 2020) - Kireyeu, V; Aichelin, J; Bratkovskaya, E; Kolesnikov, V; Mudrokh, A; Vasendina, V; Zinchenko, A
Abstract: Strangeness and hypernuclei production in heavy-ion collisions is presently under active experimental and theoretical investigation and is of particular interest for the experiments at the new acceleration complex NICA (Nuclotron-based Ion Collider fAcility) which is under construction at the Joint Institute for Nuclear Research (Dubna, Russia). We study the production of (hyper)nuclei in the NICA energy range using a novel n-body dynamical transport approach called Parton-Hadron-Quantum-Molecular Dynamics (PHQMD).